The Influence of Tik Tok Content Marketing on Brand Awareness Warung Kihaji, Sumedang City - Priansa, Donni Juni; Putra, Yoga Pasha Koswara (Jurnal Wacana Ekonomi, 2023)
The use of Content Marketing in businesses that have followed today's times have used a lot of social media in introducing products or services offered by businesses to increase Brand Awareness among consumers at large to increase purchasing power in their businesses. Social media that is now widely used in Content Marketing is Tiktok Social Media which shows short videos widely introducing their business. One of the businesses that uses Content Marketing in running their business is Warung KiHaji which is in Sumedang. This study aims to determine the extent to which Content Marketing made by Warung KiHaji increases Brand Awarness among consumers. This research is quantitative, which is described by descriptive verification. Descriptive is used to explore variables. The population of this study is consumers in Sumedang City who have seen media accounts and promotional videos on Warung KiHaji Social Media accounts with a total sample of 100 samples. This research found that Content Marketing created by Warung KiHaji is in a high category; Brand Awarnees Warung KiHaji is in the sufficient category; and Content Marketing has a significant effect on Brand Awarnees Warung KiHaji with a very strong level of influence classification.